Assessing the Effectiveness of Manual Handling Training in Reducing Forceful Exertion for Workers in a Medical Device Manufacturing Company - Mirza Amirah Mohamed; Mohd Dzulkifli , Syahrun Neizam; Ahmad Muhaimin Mohd Said (Progress in Engineering Application and Technology, 2025)
Workplace ergonomics is important for ensuring employee health and safety, especially in industries involving manual handling tasks. This study evaluates the effectiveness of manual handling training in reducing forceful exertion among workers in a medical device manufacturing company. The primary objectives are to identify the prevalence of forceful exertion injuries, assess the knowledge gained from the training program and provide recommendations to sustain ergonomic practices. The research involved 20 workers from the Test Department, who regularly engage in tasks such as setting up and storing tester fixtures, motor boxes, ICT jigs and relocating stabilizers, all of which require significant physical effort. A mixed-method approach was employed, combining document reviews, self-assessment surveys and pre- and post-training evaluations. An Ergonomic Risk Assessment (ERA) conducted by an external assessor identified forceful exertion as a significant risk factor, recommending manual handling training to mitigate these risks. The findings revealed that lower back and foot discomfort were prevalent among workers, primarily due to repetitive heavy lifting and prolonged standing. The manual handling training significantly improved worker’s knowledge, as evidenced by the increase in post-training test scores. The paired t-test analysis confirmed a statistically significant difference between pre- and post training scores, indicating the knowledge gained from the training. Feedback from participants was overwhelmingly positive, highlighting the training’s relevance and applicability to their work. Recommendations include organizing cross-training events, conducting more practical sessions, displaying lifting weight guidelines to enhance ergonomic awareness and implementing scissor lifter trolleys or step stools to reduce ergonomic risks.